61‐2: Weakening Micro‐Cavity Effects in White Top‐Emitting WOLEDs with Semitransparent Metal Top Electrode. Issue 1 (30th May 2018) - Jiao, Zhiqiang; Huang, Qingyu; Zhan, Hongsheng; Jin, Xin; Wang, Lu; Yuan, Guangcai
Abstract : Top emitting white organic light emitting diodes (WOLEDs) hold great promise for high brightness and high resolution active matrix OLED displays. One key challenge of high‐performance top emitting WOLEDs is the availability of top electrodes with superior optical, electrical properties. Herein, we demonstrate the improvement of both electrical and optical properties of widely used metal electrode, which is achieved by co‐depositing a proper amount of magnesium (Mg) with silver (Ag) deposition with optimized deposition rate of both Mg and Ag. Corresponding WOLEDs are fabricated using this optimized 80Å thick Mg:Ag electrode, which show a 14.73% enhanced current efficiency at 10mA/cm 2 compared to their 120Å thick Mg:Ag electrode counterparts. Also, the 80Å thick Mg:Ag based WOLEDs show close‐to‐identical emission spectra at different view angles and color shift.